Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1155/2020/8816191
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Hydrodynamic Forces on the Identification of the Rotor-Stator-Rubbing Fault in a Rotating Machinery

Abstract: Mechanical failures of a complex machine such as rotor widely used in severe conditions often require specialized knowledge, technical expertise, and imagination to prevent its rupture. In this paper, a model for analyzing excitation of a coupled lateral-torsional vibrations of a shaft system in an inviscid fluid is proposed. The model considers the recurrent contact of the vibrating shaft to a fixed stator. The simplified mathematical model of the rotor-stator system is established based on the energy princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…The higher harmonic resonance at 1× order (47.21 Hz) can be observed in the two unbalanced rotors. However, it is worth mentioning from the FFT spectral plot that the higher sup-harmonic frequencies, for example, 2×, 4×, 6×, etc., along with the 1/2× subharmonic, which usually arise due to the rubbing presence as indicated in [10,18], do not appear in this case. It is evident that the decomposition by FFT is not satisfactory enough as some irregular and imprecise fluctuations exist around the critical frequency levels.…”
Section: Vibration Response Of the Coupled System With Rubbing Faultmentioning
confidence: 74%
See 2 more Smart Citations
“…The higher harmonic resonance at 1× order (47.21 Hz) can be observed in the two unbalanced rotors. However, it is worth mentioning from the FFT spectral plot that the higher sup-harmonic frequencies, for example, 2×, 4×, 6×, etc., along with the 1/2× subharmonic, which usually arise due to the rubbing presence as indicated in [10,18], do not appear in this case. It is evident that the decomposition by FFT is not satisfactory enough as some irregular and imprecise fluctuations exist around the critical frequency levels.…”
Section: Vibration Response Of the Coupled System With Rubbing Faultmentioning
confidence: 74%
“…The first dynamic response of the misaligned Cardan shaft is performed. To validate the proposed model in this study, the parameters for the numerical simulation are chosen to be the same as those of the experiment in [10], and the proportionality between ω and Ω is maintained for a wide range of Ω, which is the threshold (ω = Ω). To illustrate the numerical results, the following plots in Figures 7 and 8 are used.…”
Section: Vibration Analysis Of the Unbalanced Rotors Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The work of [8] presented a state estimation method using ensemble empirical mode decomposition to identify the operating state of a cardan shaft in high-speed trains by collecting two sets of gearbox vibration signals. Most studies have concentrated on the behavior of mechanisms coupled to universal joints [9][10][11][12][13]. However, there have been many cases of failure associated with the malfunctioning driveshaft in practice, and a limited article can be found that addresses this specific topic of cardan shaft failure in a fluid medium [5,14].…”
Section: Introductionmentioning
confidence: 99%
“…The recently published numerical study of this model concluded that the vibration generated by Hooke's joint and the strong fluctuation of the connected rotors are proportional to the transient stiffness of the flexible drive shaft [4][5][6][7][8][9][10][11][12][13][14][15]. In the present experimental study of a cracked driveshaft interconnected via Hooke's joint, it is important to consider the effect of fluid properties, shaft geometry, and speed.…”
Section: Introductionmentioning
confidence: 99%